FAKTOR YANG MEMPENGARUHI PENGEMBANGAN BAKAT AKADEMIK PESERTA DIDIK DI SMP 11 PADANG - NIATI, EFATRICIA; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The research is based on the phenomena the researchers found in the field through interview with the adviser teachers and also the subject teachrs on October 2011, it is acqussed vadrousÂ information that the learners at SMPN 11 Padang there were many learners which got grade under the mini mastery criteria (KKM ) in certain fseld. This meant that the learning result they got were below their potential or intellectual ability they actually possess. The result of the research were 1) Internal factor based on interest in achievement learning motivation,willingness in taking a risk in elaborating academic interest diligence in facing academic challenge by 51,15 %. 2) External factor based on maximum oppostunity to elaborak one self in getting achsevement,facility psepased by parents in elaborating the learners, ability,suppst from family in helping learners in elaborating learners, ability,living environment,and also pasentings guidance in motivating by 45,98%.